Secular and religious coping strategiesin women: the age-related aspect - Partyko, Tetiana B.; Iesyp, Mariana Z. (Journal of Education Culture and Society, 2020)
This article highlights the research fi ndings of the peculiarities of using secular and re-ligious coping strategies by women of different age groups (from age 19 to 70). Focusing on describing age dynamics in coping strategies, it shows that the tendency to use one or other methods of coping with diffi culties is age-related. The research revealed the differences with regard to the object of control in problematic situations and resource origin between two age groups: early and late adulthood. Additionally, it is assumed that women’s subjec-tive resource of overcoming diffi culties includes emotional self-control, while their objective resource–educational level and employment.